2017
DOI: 10.1002/2017jf004197
|View full text |Cite
|
Sign up to set email alerts
|

Self‐organized kilometer‐scale shoreline sand wave generation: Sensitivity to model and physical parameters

Abstract: The instability mechanisms for self‐organized kilometer‐scale shoreline sand waves have been extensively explored by modeling. However, while the assumed bathymetric perturbation associated with the sand wave controls the feedback between morphology and waves, its effect on the instability onset has not been explored. In addition, no systematic investigation of the effect of the physical parameters has been done yet. Using a linear stability model, we investigate the effect of wave conditions, cross‐shore prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…Thus, we here explore two values, D c = 0.6 m and D c = 0.75 m. Regarding the shape of the bathymetric perturbation a linear decay in bed level from 1 at the shoreline to 0 at D c is considered. The effect of different shape functions on model shoreline sand wave formation is discussed in Idier et al (2017). Regarding the wave conditions we use the SWAN outputs in case of SW breeze as a reference.…”
Section: Large Scale Shoreline Undulationsmentioning
confidence: 99%
“…Thus, we here explore two values, D c = 0.6 m and D c = 0.75 m. Regarding the shape of the bathymetric perturbation a linear decay in bed level from 1 at the shoreline to 0 at D c is considered. The effect of different shape functions on model shoreline sand wave formation is discussed in Idier et al (2017). Regarding the wave conditions we use the SWAN outputs in case of SW breeze as a reference.…”
Section: Large Scale Shoreline Undulationsmentioning
confidence: 99%
“…Kaergaard and Fredsoe, 2013a) and on the shape of the bathymetric undulations associated to the shoreline undulations (Idier et al, 2017). In this section we adopt the value θ c = 45 • for being representative of most of the predicted values.…”
Section: Correlation Between Shoreline Sand Wave Presence and High-anmentioning
confidence: 99%
“…For this bathymetric perturbation, called P 2, the cross-shore amplitude of the depth contours beyond the surf zone can be larger than the amplitude of the perturbed shoreline (for certain profiles). The influence of this choice in the formation of KSSW has been investigated thoroughly by Idier et al (2017). It was found that low-angle waves can be de-stabilizing only for the perturbation P 2.…”
Section: Justification Of the Setup Chosen In The 1dmorfo Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…When prevailing waves approach from "low angles" (relative angles less than the flux-maximizing angle), gradients in alongshore transport tend to diverge at convex-seaward (promontory) segments of the shoreline, causing erosion, and converge at concave-seaward (embayed) segments, causing accretion (Ashton et al, 2001;Ashton & Murray, 2006a;Arriaga et al, 2017;Falqués, 2003). Conversely, under a "high angle" wave climate, these gradients in net sediment transport are reversed, such that large-scale coastline curvature tends to increase over time and emergent planform features develop (Ashton et al, 2001;Ashton & Murray, 2006a, 2006bFalqués, 2003;Idier et al, 2017;Murray & Ashton, 2013;van den Berg et al, 2012). In most locations, on some days, the offshore waves approach from high angles relative to the local shoreline orientation, and on some days, they approach from low angles.…”
Section: Introductionmentioning
confidence: 99%